2007
DOI: 10.1117/1.2772652
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vulnerable plaques by multiphoton microscopy

Abstract: Cardiovascular disease is the primary cause of death in the United States; the majority of these deaths are caused by the rupture of vulnerable plaques. An important feature of vulnerable plaques is the thickness of the fibrous cap that covers the necrotic core. A thickness of less than 65 microm has been proposed as a value that renders the plaque prone to rupture. This work shows that multiphoton microscopy (MPM) can image the plaque with microm resolution to a depth deeper than 65 microm. The fibrous cap em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 28 publications
(28 reference statements)
2
53
0
Order By: Relevance
“…In previous work, nonlinear microscopy, using combined SHG and TPEF imaging, was shown to reveal structural collagen and elastin fi bers of the extracellular matrix in the arterial wall, the site of atherosclerotic plaque development ( 4,12,24,25 ). In addition, Wang et al demonstrated that SHG/TPEF/CARS imaging can be used to identify endothelial and smooth muscle cells in the arterial wall ( 26 ).…”
Section: Atherosclerotic Apoe-defi Cient Mouse Modelmentioning
confidence: 99%
“…In previous work, nonlinear microscopy, using combined SHG and TPEF imaging, was shown to reveal structural collagen and elastin fi bers of the extracellular matrix in the arterial wall, the site of atherosclerotic plaque development ( 4,12,24,25 ). In addition, Wang et al demonstrated that SHG/TPEF/CARS imaging can be used to identify endothelial and smooth muscle cells in the arterial wall ( 26 ).…”
Section: Atherosclerotic Apoe-defi Cient Mouse Modelmentioning
confidence: 99%
“…Megens et al (2008) and Doras et al (2011) investigated the changes in collagen structure inside an artery wall affected by atherosclerosis using reconstructions of multiphoton images as well as optical polarization state analysis. Using excised human aortas, Lilledahl et al (2007) demonstrated combined TPEF and SHG imaging of fibrous caps to predict plaque vulnerability. This work showed en face NLOM imaging of plaque to a depth beyond 65 μm from the lumen face through the fibrous cap in thincapped fibroatheroma and into the lesion core, clearly demonstrating the potential of NLOM to differentiate between vulnerable and stable plaques.…”
Section: Tpef and Shg Imagingmentioning
confidence: 99%
“…Maffia et al (2007) reported a threedimensional imaging of the entire structure of an isolated intact ApoE−/− mouse carotid artery, identifying a homed, fluorescently tagged, adoptively transferred lymphocytes. Based on a measure of the collagen to elastin density ratio (or SHG:TPEF intensity ratio), Lilledahl et al (2007) and Smith et al (2009) developed an approach to detect vulnerable plaques based on the assumption of a higher collagen density in atherosclerosis lesions, especially in fibroatheroma, compared to the normal vessel wall. Using histological specimens as a reference, Lilledahl et al (2007) reported a specificity of 81 % in detecting fibrous cap atheroma using collagen to elastin ratios derived from pixel-based image quantification.…”
Section: Tpef and Shg Imagingmentioning
confidence: 99%
See 2 more Smart Citations